Nigeria's Federal Character Commission (FCC): a critical appraisal. (1st October 2020) - Demarest, Leila; Langer, Arnim; Ukiwo, Ukoha
ABSTRACT: Since attaining independence, Nigeria has experienced recurrent tensions due to the severe horizontal inequalities that exist between different regions and ethnic groups. After the end of the Biafran civil war, consecutive regimes embarked on a reform process intended to address the sensitive issues of inequality and ethnic domination. Key reforms included the adoption of the federal character principle to ensure the equitable representation of different groups in all tiers of government, and the formation of the Federal Character Commission (FCC) to monitor and enforce its implementation. While the FCC has raised hopes on redressing historical imbalances in Nigeria's civil service, this paper finds that little progress has been made over time. The workings of the FCC remain plagued by legal and administrative constraints, chronic underfunding, and political dependence. These issues will need to be addressed if the FCC wants to gain the legitimacy and power needed to fulfil its mandate.